RSD931, a novel anti-tussive agent acting on airway sensory nerves - Adcock, J J (2003)
1. The anti-tussive effects, of the local anaesthetic, lidocaine and carcainium chloride (RSD931) have been investigated in guinea-pigs and rabbits. 2. Pre-treatment of guinea-pigs with aerosols of lidocaine or RSD931 at 0.1, 1.0 and 10 mg ml(−1) reduced the number of citric acid-induced coughs by 9.3, 32.6 and 40.9% (P>0.05) for lidocaine and by 25.3% (P>0.05), 40.4% (P>0.05) and 97.6% (P<0.01) for RSD931, respectively and increased the latency to onset of cough at 10.0 mg ml(−1) only. In addition, RSD931 at 10 mg ml(−1) reduced citric acid-evoked cough responses in rabbits (with prior exposure to ozone at 3 p.p.m. for 1 h) from 22.1±5.1 to 2.7±0.9 coughs (P<0.01). 3. Acute pre-treatment of guinea-pigs with aerosols of lidocaine or RSD931 at 10.0 and 30.0 mg ml(−1) reduced the number of capsaicin-evoked coughs by 42.2 and 10.3% (P>0.05) (lidocaine) and by 25% (P>0.05) and 76.9% (P<0.01) (RSD931), respectively. Lidocaine had little effect on the latency of cough onset at either 10.0 or 30.0 mg ml(−1), however, RSD at 30.0 mg ml(−1) significantly (P<0.05) prolonged the latency of cough onset. 4. RSD931 (10.0 mg ml(−1)) significantly (P<0.05–<0.01) reduced the spontaneous and histamine-evoked discharges in Aδ-fibres originating from airway, rapidly adapting stretch receptors (RARs) without affecting histamine-evoked bronchoconstriction. Lidocaine at 10.0 mg ml(−1) also significantly (P<0.05) inhibited the spontaneous and histamine-induced discharges of RARs without affecting histamine-evoked bronchoconstriction. 5. Aerosols of RSD931 (10.0 mg ml(−1)) caused a transient, but significant (P<0.05), activation of pulmonary C-fibre endings 2.5 min after administration started. RSD931 had no significant (P>0.05) effects on discharges in bronchial C-fibres originating from bronchial C-fibre endings, capsaicin-evoked discharges of either pulmonary or bronchial C-fibre endings or on capsaicin-evoked bronchoconstriction. In contrast, lidocaine (10.0 mg ml(−1)) significantly (P<0.05) inhibited spontaneous and capsaicin-induced discharges in both pulmonary and bronchial C-fibres respectively. Lidocaine also significantly (P<0.05) reduced capsaicin-evoked bronchoconstriction. 6. These studies suggest that the anti-tussive actions of RSD931 are mediated via inhibition of discharges in Aδ-fibres originating from airway RARs. The mechanism of action of RSD931 is distinct from that of the local anaesthetic lidocaine and RSD931 may represent a novel class of anti-tussive agent.